Utilization of Astaxanthin as a Synthetic Antioxidant Replacement for Emulsified Sausages - Jin-Kyu Seo (Antioxidants, 2021)
The aim of this study was to evaluate the effect of astaxanthin (AX) on the quality and sensory characteristics of emulsified pork sausages during cold storage. The changes of Peroxide value (PV), 2-thiobarbituric acid-reactive substances (TBARS), thiol content, texture profile analysis, instrumental color, and sensorial qualities were assessed on specific storage days. The emulsified sausages with added AX exhibited significantly (p < 0.05) higher redness values and total color differences (ΔE) on all storage days. Sensory values recorded the reddest color and greater overall acceptability scores to the sample with AX. In addition, AX had a significantly (p < 0.05) greater effect on PV, TBARS, and thiol content of sausages, compared with the control (CON). AX showed higher oxidation stability than CON for regression coefficient, and the level of inhibition of malondialdehyde formation was similar to that of butylated hydroxytoluene (BHT) on storage days. Synthetically, AX had a desirable consequence on antioxidant activity and color of emulsified sausages; therefore, it can be used as a multifunctional additive in emulsified pork sausages.